Synthesis of potassium pentagamavunonat-0 using potassium hydroxyde and solvent tertrahydrofuranethanol - Supardjan Amir Margono; Ester Yani Verawati (Indonesian Journal of Pharmacy, 2005)
Pentagamavunon-0 (PGV-0) (2,5-bis(4’-hydroxy-3’-methoxy benzy-lidene) cyclopentanone) is a curcumin analogue. To improve its bioavailability it has been succesfully synthesized the Na-salt of this compound. However, sodium may disturb the electrolyte liquid-balance in the body which in turn hypertension. Therefore, the synthesis of potassium pentagamavunonat-0 is attempted. Synthesis has been done using potassium hydroxide as a potassium source, in tetrahydrofuran-ethanol solvent, with molar variations. The result is dipotassium pentagamavunonate-0 (elucidated with IR, 1H-NMR, 13C-NMR and MS spectra), which is more soluble in water and has better stability at high pHs. Molar variations did not show correlation with its yield. The yields are more than 100 %, may be caused by water crystals that contaminate the compound. Key words : pentagamavunon-0, dikalium pentagamavunonat-0, synthesis